An Improved Integral Method for Prediction of Distorted Inlet Flow Propagation in Axial Compressor - Eddie Yin-Kwee Ng; Ningyu Liu; Hong Ngiap Lim; Daniel Tan (International Journal of Rotating Machinery)
An improved integral method is proposed and developed for the quantitative prediction of distorted inlet flow propagation through axial compressor. The novel integral method is formulated using more appropriate and practical airfoil characteristics, with less assumptions needed for derivation. The results indicate that the original integral method (Kim et al., 1996) underestimated the propagation of inlet flow distortion. The effects of inlet flow parameters on the propagation of inlet distortions as well as on the compressor performance and characteristic are simulated and analyzed. From the viewpoint of compressor efficiency, the propagation of inlet flow distortion is further described using a compressor critical performance and its associated critical characteristic. The results present a realistic physical insight to an axial-flow compressor behavior with a propagation of inlet distortion.